The miR-17-92 cluster: Yin and Yang in human cancers. (2022) - Zhao, Wenyuan; Gupta, Ananya; Krawczyk, Janusz; Gupta, Sanjeev
Highlights: The miR-17-92 cluster functions both as oncogenes and tumour suppressors. The mechanisms regulating the expression of miR-17-92 cluster are discussed. MiR-17-92 cluster members exert specific and overlapping effects in cancers. Functions of miR-17-92 cluster depend on cancer types and target mRNAs. Abstract: MicroRNAs (miRNAs) are non-coding RNAs which modulate gene expression via multiple post-transcriptional mechanisms. They are involved in a variety of biological processes, including cell proliferation, metastasis, metabolism, tumorigenesis, and apoptosis. Dysregulation of miRNA expression has been implicated in human cancers, and they may also serve as biomarkers of disease progression and prognosis. The miR-17-92 cluster is one of the most widely studied miRNA clusters, which was initially reported as an oncogene, but was later reported to exhibit tumour suppressive effects in some human cancers. This review summarizes the recent progress and context-dependant role of this cluster in various cancers. We summarize the known mechanisms which regulate miR-17-92 expression and molecular pathways that are in turn controlled by it. We discuss examples where it acts as an oncogene or a tumour suppressor along with key targets affecting hallmarks of cancer. We discuss how cellular contexts regulate the biological effects of miR-17-92. The plausible mechanisms of its paradoxical roles are explained, and mechanisms are described that may contribute to cell fate regulation by miR-17-92. Further, we discuss recently developed strategies to target miR-17-92 cluster in human cancers. MiR-17-92 may serve as a potential biomarker for prognosis and response to therapy as well as a target for cancer prevention and therapeutics.